TemporalMixFormer: Spatiotemporal Spectral Unmixing for Multi-Date Hyperspectral Earth Observation Using Dynamic State-Space Networks (Journal of Advanced Artificial Intelligence Research, 2026)
Multi-date hyperspectral Earth observation provides rich spectral and temporal information for land cover monitoring, but the spatial resolution of such sensors often results in mixed pixels where multiple materials contribute to a single spectral measurement. Spectral unmixing, the process of decomposing mixed pixels into constituent endmembers and their abundances, becomes significantly more challenging when temporal dynamics are introduced because land cover transitions, phenological cycles, and varying illumination conditions induce non-stationary mixing patterns over time. Existing unmixing approaches typically process each date independently or rely on simplistic temporal smoothing, failing to capture the underlying state-space structure governing the evolution of abundances. This paper presents TemporalMixFormer, a novel architecture that integrates state-space modeling with multi-head attention mechanisms to perform spatiotemporal spectral unmixing across multi-date hyperspectral imagery. TemporalMixFormer treats abundance trajectories as latent states that evolve according to a learned dynamic system, while a transformer-inspired mixing module adaptively weights spectral contributions from different acquisition dates. The system is designed as a scalable, modular framework suitable for large-scale operational deployment, with explicit considerations for computational efficiency, sensor interoperability, and temporal irregularity. We discuss architectural trade-offs between expressiveness and inference speed, the role of prior knowledge in regularizing abundance dynamics, and strategies for ensuring robustness under cloud cover, atmospheric variability, and missing observations. The paper further examines the broader implications of deploying such a model within Earth observation data cubes, including data governance, fairness across geographic regions, environmental sustainability of model training, and policy alignment with global monitoring initiatives such as the Sustainable Development Goals. By uniting state-space theory with modern deep learning components, TemporalMixFormer offers a principled path toward temporally coherent, physically interpretable unmixing at continental scales.
Keywords: hyperspectral unmixing, spatiotemporal modeling, state-space networks, multi-date Earth observation, dynamic systems, deep learning, spectral mixture analysis, land cover change, remote sensing, data governance